CARDIAC SURGERYNew oral anticoagulants – a practical guide - Ciurus, Tomasz; Sobczak, Sebastian; Cichocka-Radwan, Anna; Lelonek, Malgorzata (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2015)
Oral direct inhibitors of thrombin and activated factor Xa are approved as new anticoagulant drugs. In contrast to vitamin K antagonists (VKA) and heparins, the new agents have single targets in the coagulation cascade and more predictable pharmacokinetics, but they lack validated and available antidotes. Unlike VKA, they do not require routine monitoring of coagulation. However, the measurement of their pharmacologic effects might be of value in selected patients. They interfere with the routine coagulation tests, which should be interpreted with caution. Specific tests exist and can be used in case of emergencies. Adequate supportive care and temporary removal of all antithrombotic agents constitute the basis for management of serious bleeding complications. The administration of coagulation factors, such as fresh frozen plasma, prothrombin complex concentrates or recombinant activated FVII, can benefit in life-threatening bleeding or emergency surgery. Specific antidotes for non-vitamin K oral anticoagulants are in clinical development.